ANALISIS SISTEM AKTIVITAS FREIGHT FORWARDING BERBASIS ACTIVITY SYSTEM THEORY PADA TERMINAL PETI KEMAS SURABAYA - Rosyidatul Auliyah; Veronika Kiky Anggaini Anggaini; Nabila Amintia Amintia; Defira Febriana Febriana; M. Fadly Yudha Siahaya Siahaya; Lunariana Lubis Lubis (Program Studi Administrasi Negara, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Warmadewa, 2026)
This study analyzes freight forwarding activities at PT Terminal Peti Kemas Surabaya in response to the increasing international and domestic container throughput in 2025. The background of this research is based on the consistent growth of container flows exceeding one million TEUs annually, along with month-on-month and year-on-year fluctuations that require an adaptive and integrated logistics work system. The study aims to comprehensively examine freight forwarding activities using the Activity System Theory developed by Yrjö Engeström by mapping six core components: subject, object, mediating artifacts (tools), rules, community, and division of labor. This research employs a descriptive qualitative approach with a case study strategy. Data were collected through documentation of operational performance reports, port regulations, and terminal throughput statistics, and analyzed using an interactive analysis model consisting of data reduction, data display, and conclusion drawing. The findings indicate that the increase in throughput—approximately 3% in the first semester of 2025 and up to 13% during peak periods—was supported by competent operational actors, optimized container transformation processes, the implementation of the Terminal Operating System (TOS), and strong coordination among port stakeholders. However, systemic contradictions were identified, including yard capacity pressure, potential yard congestion, and procedural misalignment during peak volume periods. The novelty of this research lies in integrating quantitative throughput trend analysis with the Activity System framework to holistically reveal the internal dynamics of freight forwarding operations, thereby contributing theoretically to port logistics studies and practically to improving terminal performance and competitiveness.